2013
DOI: 10.1139/cjpp-2012-0422
|View full text |Cite
|
Sign up to set email alerts
|

Ageing-induced decrease in cardiac mitochondrial function in healthy rats

Abstract: It is widely recognized that mitochondrial dysfunction is a key component of the multifactorial process of ageing. The effects of age on individual components of mitochondrial function vary across species and strains. In this study we investigated the oxygen consumption, the mitochondrial membrane potential (Δψ), the sensitivity of mitochondrial permeability transition pore (mPTP) to calcium overload, and the production of reactive oxygen species (ROS) in heart mitochondria isolated from old compared with adul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
0
32
0
2
Order By: Relevance
“…This is thought to be due to slowed electron transport and prolongation of ubisemiquinone radical occupancy in the complex [57]. However, most studies with animal models have reported a decrease in Dw with aging [58,59]. Therefore the Dw factor cannot explain the rise in ROS production in older subjects.…”
Section: Aging and Oxidative Stressmentioning
confidence: 84%
“…This is thought to be due to slowed electron transport and prolongation of ubisemiquinone radical occupancy in the complex [57]. However, most studies with animal models have reported a decrease in Dw with aging [58,59]. Therefore the Dw factor cannot explain the rise in ROS production in older subjects.…”
Section: Aging and Oxidative Stressmentioning
confidence: 84%
“…Indeed, pharmacological mPTP inhibitors failed to produce significant effects in either normal or stressed conditions. For instance, cyclosporin A (CsA) was unable to inhibit carboxyatractyloside‐induced permeability transition in aged mitochondria (García, Zazueta, Martínez‐Abundis, Pavón, & Chávez, 2009) and to prolong the time necessary to induce mPTP opening in isolated mitochondria (Duicu et al., 2013) and in cardiomyocytes isolated from old rats (Liu, Zhu, Brink, Glass, & Rebecchi, 2011). Similarly, the ability of sevoflurane and isoflurane conditioning (Li et al., 2013; Zhu et al., 2010) and of the GSK‐3β inhibitor SB‐216763 (Zhu, Rebecchi, Glass, Brink, & Liu, 2011) to protect against myocardial ischemia–reperfusion injury, which is mediated by inhibition of mPTP opening in young rats, is abrogated in senescent animals.…”
Section: Experimental Evidence Supporting the Involvement Of The Mptpmentioning
confidence: 99%
“…Ventricular tissue was manually triturated with subtilisin (5 mg/g wet tissue), a non-specific protease, to release the interfibrillar mitochondria. The suspension was homogenised with a tissue homogenizer (Glas-Col 099C K5424 CE) for maximum 30 s. The final tissue homogenate obtained was processed at 4°C using the differential centrifugation technique as previously described (Duicu et al 2013). Mitochondrial protein concentration was determined using biuret method (Gornall et al 1949).…”
Section: Rat Heart Mitochondria (Rhm) Isolationmentioning
confidence: 99%
“…The substrate-uncoupler-inhibitor-titration (SUIT) protocol, GM State2 + ADP OXPHOS + c + Omy State4 + FCCP ETS + (Ama) ROX , was previously described (Duicu et al 2013) and comprised the following steps: (i) addition of complex I respiratory substrates, 10 mmol/L glutamate (G) and 2 mmol/L malate (M), State 2 (basal respiration); (ii) addition of 5 mmol/L adenosine diphosphate (ADP) to assess the maximal oxidative phosphorylation capacity (OXPHOS), State 3 (active respiration); (iii) addition of 10 mol/L cytochrome c (c) to check for the integrity of mitochondrial outer membrane; (iv) addition of 2 g/mL oligomycin (Omy), an F 0 F 1 -ATP synthase inhibitor, to inhibit State 3 at the level of State 4; (v) successive titrations (0.5 mol/L steps) with FCCP (carbonyl cyanide p-(trifluoro-methoxy) phenyl-hydrazone) to obtain the uncoupled respiration and to measure the electron transport system capacity, ETS; (vi) inhibition of respiration with 2.5 mol/L antimycin A (Ama) to measure the residual oxygen consumption, ROX state. Mitochondrial respiration was corrected for oxygen flux due to instrumental background and ROX.…”
Section: High-resolution Respirometry Experimentsmentioning
confidence: 99%
See 1 more Smart Citation